The mathematical modelling and simulation of a conventional single main rotor helicopter and the identification of its linear models - Siepker, E. B. J.(Eugen Bernard Johan) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Ing.) -- University of Stellenbosch, 1990.